Soft Computing for Risk Evaluation and Management Applications in Technology, Environment and Finance - Ruan, Da 1960-2011; Kacprzyk, Janusz 1947-; Fedrizzi, Mario 1949- (Studies in Fuzziness and Soft Computing, 2001)
Risk is a crucial element in virtually all problems people in diverse areas face in their activities. It is impossible to find adequate models and solutions without taking it into account. Due to uncertainty and complexity in those problems, traditional "hard" tools and techniques may be insufficient for their formulation and solution. This is the first book in the literature that shows how soft computing methods (fuzzy logic, neural networks, genetic algorithms, etc.) can be employed to deal with various problems related to risk analysis, evaluation and management in various fields of technology, environment and finance